Discretionary loan loss provision in the Moroccan banking sector: The role of governance mechanisms - El Mokrani, Yousra; El Idrissi, Issam; Alami, Youssef (goodwood publishing, 2021)
Purpose: The present paper aims to examine the impact of corporate governance mechanisms on earnings management extent in the Moroccan banking sector. Research methodology: This research investigates the relationship between listed banks' governance mechanisms and earnings management in the CSE over the period 2017-2020. This study relies on a two-step quantitative approach, which consists firstly of estimating discretionary loan loss provisions to measure EM, then presenting the association between banks’ governance mechanisms and discretionary loan loss provisions. Results: The findings indicate that board size, gender diversity, audit committee’s independence, and state ownership constraint EM practices among the Moroccan listed banks. While other governance mechanisms, such as institutional ownership and board activity, seem to have no significant effect on restraining managers’ discretionary behavior. Limitations: Many qualitative and quantitative factors could influence discretionary loan loss provisions and not only the used variables in this research. Contribution: This research reveals the need to maintain the vigilant supervision of the regulatory framework to limit these opportunistic practices in the local banking industry. Also, our study has important implications for establishing a new set of governance requirements such as board diversity in Morocco.